PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPS KELAS IV SD NEGERI KADU SEMPUR - Rusmiati, Sihury Wellya Pamungkas; Latifah, Nur; Fadillah, Ahmad Arif (Jurnal Pendidikan Dasar, 2023)
This study aims to determine the effect of the two stay two stray (TSTS) learning model on the learning outcomes of grade IV social studies subjects at SDN Kadu Sempur. This research is quantitative research using quasi-experimental research methods with pretest-postest. The population subjects in this study were grade IV students at SD Negeri Kadu Sempur by taking samples of two classes as many as 32 class IV B students as a control class and 32 grade IV A students as an experimental class. So it can be concluded "There is an influence of the two stay two stray learning model on student learning outcomes in grade IV social studies subjects of SDN Kadu Sampur". The results of the hypothesis testing study using paired sample t-test, for testing the posttest hypothesis from the results of the t-test obtained Tcalculate = 5.01. And it can be known the value of ttable 1.66. Based on the hypothesis that has been formulated earlier, it can be known that the calculated value of ttable > then 5.01 > 1.66. Thus H1 is accepted and H0 is rejected.